Detection of Two Iflaviruses of the Honeybee Apis mellifera in the Northern Regions of Ukraine - Rud, Y.P.; Buchatsky, L.P.; Lazarenko, L.M.; Odnosum, H.V.; Yefimenko, T.M.; Vasilenko, O.G.; Spivak, M.Y.; Safronova, L.A.; Рудь, Ю.П.; Бучацький, Л.П.; Лазаренко, Л.M.; Односум, Г.В.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
The aim of this study was to investigate the spread of iflaviruses in the western honeybee Apis mellifera in the northern regions of Ukraine. Methods. The study involved systematic visual inspections of apiaries in the specified regions. The distribution of iflaviruses, particularly Sacbrood Virus (SBV) and Deformed Wing Virus (DWV), was examined at private apiaries in the Kyiv, Zhytomyr, and Chernihiv regions. RNA was extracted from larvae and underdeveloped imago bees taken from brood cells to perform polymerase chain reaction (PCR). The ProtoScript First Strand cDNA Synthesis Kit (NEB) was used for cDNA synthesis according to the manufacturer’s instructions. Oligonucleotide primers specific to the gene fragment encoding the capsid protein were used to identify the SBV iflavirus, while the DWV iflavirus was identified through a fragment of the RNA-dependent RNA polymerase gene. Conclusions. The SBV and Deformed Wing Virus (DWV) were detected using PCR in the western honeybee Apis mellifera in three northern regions of Ukraine – Chernihiv, Kyiv, and Zhytomyr. Given the potential for co-infection between these two iflaviruses (DWV + SBV), further research is needed to explore the mechanisms of interaction between these viruses and the immune response of honeybees.